Anxiety, depression, and quality of life in children and adults with alopecia areata: A systematic review and meta-analysis - van Dalen, Marije; Muller, Kirsten S.; Kasperkovitz-Oosterloo, Johanna M.; Okkerse, Jolanda M. E.; Pasmans, Suzanne G. M. A. (Frontiers in Medicine, 2022)
Introduction Alopecia areata (AA) is a non-scarring hair loss condition, subclassified into AA, alopecia universalis, and alopecia totalis. There are indications that people with AA experience adverse psychosocial outcomes, but previous studies have not included a thorough meta-analysis and did not compare people with AA to people with other dermatological diagnoses. Therefore, the aim of this systematic review and meta-analysis was to update and expand previous systematic reviews, as well as describing and quantifying levels of anxiety, depression, and quality of life (QoL) in children and adults with AA. Methods A search was conducted, yielding 1,249 unique records of which 93 were included. Results Review results showed that people with AA have higher chances of being diagnosed with anxiety and/or depression and experience impaired QoL. Their psychosocial outcomes are often similar to other people with a dermatological condition. Meta-analytic results showed significantly more symptoms of anxiety and depression in adults with AA compared to healthy controls. Results also showed a moderate impact on QoL. These results further highlight that AA, despite causing little physical impairments, can have a significant amount on patients’ well-being. Discussion Future studies should examine the influence of disease severity, disease duration, remission and relapse, and medication use to shed light on at-risk groups in need of referral to psychological care. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42022323174].